The Effect of Current Ratio, Debt to Equity Ratio, and Operating Profit Margin on Price to Book Value at PT. Sinar Mas Agro Resources and Technology Tbk. Quarterly 2020-2024 - Tasya Nuranisa; Rita Tri Yusnita; Gian Riksa Wibawa (Utami Publisher, 2026)
This study aims to analyze the relationship between the Current Ratio, Debt to Equity Ratio, and Operating Profit Margin in influencing Price to Book Value when Indonesia is experiencing global economic conflict and post-pandemic recovery. This study uses quantitative research. Sampling in this study uses Purposive Sampling technique. The type of data used is secondary data with a research sample of 20 data at PT. Sinar Mas Agro Resources and Technology Tbk. The data analysis tool used is time series data regression analysis with the help of SPPSS 25 and the hypothesis is tested with the F-test and T-test with a significance level of α = 0.05 or 5%. From the results of the regression analysis, the results of the simultaneous test show that the Current Ratio, Debt to Equity Ratio, and Operating Profit Margin have a significant effect on Price to Book Value. The partial results of the Current Ratio and Debt to Equity Ratio do not have a significant effect on Price to Book Value, while Operating Profit Margin has a significant effect on Price to Book Value.